Pelaksanaan Program Parenting Tentang Pengaruh Penggunaan Gadget Terhadap Tumbuh Kembang Anak di PAUD KB Nurul Ihsan Desa Rukam Kecamatan Mendo Barat - Isro'i, Nurul Faqih (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Gadgets have a big role in children's development, both from the positive and negative sides. It is necessary to pay attention to its use so that its positive impact can be maximized and the negative impacts it causes can be avoided. This requires parents and educators at educational institutions to be able to provide understanding in accessing the internet using these gadgets. One step that educators in PAUD can provide is through a parenting program. Parents must be trained from an early age to be